2017
DOI: 10.3389/fimmu.2017.01506
|View full text |Cite
|
Sign up to set email alerts
|

Low T-Cell Responses to Mitogen Stimulation Predicts Poor Survival in Recipients of Allogeneic Hematopoietic Stem Cell Transplantation

Abstract: BackgroundSuccessful engraftment and reconstitution of the innate and adaptive immune system are associated with improved outcomes in recipients of allogeneic hematopoietic stem cell transplantation (HSCT). A clinically meaningful and simple biomarker of immunosuppression could potentially assist clinicians in their decision-making. We aimed to determine the relationship between T-cell production of interferon gamma (IFN-γ) in response to phytohemagglutinin (PHA) to clinical outcomes in HSCT recipients.Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 26 publications
2
17
0
Order By: Relevance
“…Knowing that a low IFN-γ response to phytohemagglutinin (PHA) predicts poor survival [11], I assessed CMV-specific and mitogen-induced IFN-γ release using the same commercial quantiferon-cytomegalovirus assay. Unfortunately, in the quantiferon technique, the interferon immune response after CMV-peptide-laden human leukocyte antigen (HLA) class I stimulation showed higher level than PHA-induced in the first wave of lymphocyte reconstitution (i.e., between 2–11 and 19–01), which of note, was during most intensive CMV reactivation [12].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Knowing that a low IFN-γ response to phytohemagglutinin (PHA) predicts poor survival [11], I assessed CMV-specific and mitogen-induced IFN-γ release using the same commercial quantiferon-cytomegalovirus assay. Unfortunately, in the quantiferon technique, the interferon immune response after CMV-peptide-laden human leukocyte antigen (HLA) class I stimulation showed higher level than PHA-induced in the first wave of lymphocyte reconstitution (i.e., between 2–11 and 19–01), which of note, was during most intensive CMV reactivation [12].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies in both solid and stem cell transplant recipients reported that the Quantiferon assay was frequently (up to 38%) “indeterminate” because of a poor mitogen response as a result of immunosuppression [11,13,14]. In this context, for precise interpretation of the quantiferon assay the cytometric analysis, blood count and cyclosporine (CsA) level were performed from the same blood collection (the same venipuncture) and is presented in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We found that an indeterminate QFT was associated with worse posttransplant survival. Others have shown that HCT recipients and other cancer populations with poor mitogen responses post-HCT are associated with poor outcomes [ 37 , 38 ]. Although intriguing, additional immunologic assessments, disease associations, and evaluation of other confounders need to be considered before considering the QFT mitogen response as a predictor for posttransplant outcomes.…”
Section: Discussionmentioning
confidence: 99%